HUBUNGAN PENDIDIKAN KESEHATAN DENGAN PENGETAHUAN IBU NIFAS TERHADAP POSTNATAL BREAST CARE DI WILAYAH KERJA PUSKESMAS ASTAMBUL TAHUN 2018 - Endhar Suwasih; Tut Barkinah; Isnaniah Isnaniah (Jurnal Inovasi Penelitian, 2022)
The treatment of breast during the puerperium aims to facilitate blood circulation and prevent clogging of the milk ducts so as to facilitate the release of milk. Based on the data, Banjar Regency is an area that covers exclusive breastfeeding at number 4. Astambul Health Center coverage of exclusive breastfeeding ranks 3rd out of 24 health center in Banjar Regency with a coverage of 7.26% and interviews with respondents that 66 respondents (82.5 %) massage done to the shoulder blades by non-health workers (in the container). The purpose of this study was to determine the relationship between health education and postpartum breast care knowledge in the work area of Astambul Health Center in 2019. The research design used was an analytical survey with a cross sectional approach, and the sampling technique used Saturation sampling. The instrument used is a questionnaire. Data analysis is univariate and bivariate using chi-square statistical test with α = 0.05. The results of the study of 80 respondents, most of the knowledgeable mothers were as many as 41 (51.2%) respondents. The statistical test results obtained ρ 0.043 smaller than α 0.05 means that there is a relationship between health education and knowledge of postpartum on postnatal breast care in the Work Area of Astambul Health Center in 2019. The conclusion is that there is a relationship between health education and postnatal breast care knowledge in the work area of the Astambul Community Health Center in 2019.